Italian Mediterranean Policy and Russia Between â€œRisorgimentoâ€ and the â€œGreat Warâ€ - Battaglia, Antonello (Mediterranean Journal of Social Sciences, 2011)
The Mediterranean has been an area of great importance for Italian and Russian foreign policies. The great Tsarist empire,although being landlocked, has always shown great interest for the Mediterranean Sea. In particular the Tsarist policy has been directedtoward the strategic Straits of Bosphorus and Dardanelles, whose eventual conquest would have allowed the introduction into theMediterranean routes. This policy was due to the lack of ports on "warm seasâ€. The only ports consisted of Archangel, Odessa, St.Petersburg and Riga, some of which are frozen for much of the year and at all ports rarely used. The Crimean War â€“ in which took partalso the Kingdom of Sardinia - was the first post-Napoleonic international conflict that opposed Europe to the â€œMediterraneanobjectivesâ€ of Russia. After the defeat, the Tsarist foreign policy aspirations temporarily abandoned the Mediterranean Sea, while thenascent Italy (1861) began to organize a first plan of maritime hegemony. The policies of the two powers collided in 1912 when Italy, inwar with the Ottoman Empire, in two occasions forced the Dardanelles. The Russian foreign minister, Sergei Dmitrievich Sazonovprotested strongly because Russia would not admit a new power in the Straitsâ€™s management. The moment of crisis, however, did not erasethe good relationships between the two peoples that had been consolidated into a tragic circumstance: the â€œStrait earthquakeâ€ of 1908 inwhich the city of Messina was promptly rescued by Russian sailors in practice - permitted by the government of Rome - in Italian waters.The synergy between Italy and Russia turned into an alliance in April 26, 1915 when Italy signed in London an alliance with theTriple Entente composed by Great Britain, France and Russia to fight in a war that was starting to destroy the European continent.